2015
DOI: 10.1215/00031283-3324509
|View full text |Cite
|
Sign up to set email alerts
|

Well, He May Could Have Sounded Nicer: Perceptions of the Double Modal in Doctor-Patient Interactions

Abstract: In light of Mishoe and Montgomery's 1994 analysis of the double modal's pragmatic function in mitigating face-threatening situations this article assesses the perception of the double modal in the context of a medical consultation. In an experiment using a modified matched-guise technique and a between-subjects design, a group of respondents listened to a recording of a doctor using a naturally occurring double modal in consultation with a patient, while a control group heard the same recording with one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…DMs therefore seem to be primarily used to specify and emphasize possibility modality. This finding corroborates suggestions made in the literature, especially with respect to hedging and mitigation [ 10 , 11 , 19 ]. However, necessity modals do occur in the top 10 DMs, including would , will , and should .…”
Section: Theoretical Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…DMs therefore seem to be primarily used to specify and emphasize possibility modality. This finding corroborates suggestions made in the literature, especially with respect to hedging and mitigation [ 10 , 11 , 19 ]. However, necessity modals do occur in the top 10 DMs, including would , will , and should .…”
Section: Theoretical Discussionsupporting
confidence: 92%
“…More rarely, both modals can fall on the same end of this spectrum. As for the broader pragmatic meaning of DMs, Mishoe and Montgomery [ 9 ] and DiPaolo [ 19 ] argue that DMs are used for one-on-one negotiation, face saving, and hedging, while Hasty [ 10 , 11 ] describes how DMs can be used by doctors for mitigation in their interaction with patients. There is also general agreement that DMs with may and especially might in first position are most acceptable and that these two modals rarely occur in second position [ 7 , 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The double modal construction is found mostly in Southern US English. It tends to occur during negotiation contexts, along with hedges and politeness expressions [13,14]. For example, Mishoe and Montgomery point out hedges in this example from a negotiation context "Do you think we can afford it, or should we might cancel the trip?"…”
Section: The Constructionsmentioning
confidence: 98%
“…[13]. And in an experiment, Hasty found that residents of northeast Tennesee (aged 21-75 years) judged a doctor as sounding more polite when telling a patient "We may can add the Pulmicort, which is a steroid" compared with "We may add the Pulmicort, which is a steroid" [14].…”
Section: The Constructionsmentioning
confidence: 99%
“…Double modals are of theoretical interest as they represent micro-syntactic variation that may shed light on the status of the verbal phrase: although several proposals have been made as to the constituency relations and phrase structure of double modal constructions (Boertien 1986;Battistella 1995;Hasty 2012; see also Morin et al 2020 for a discussion of double modals from the perspective of Construction Grammar), their ultimate status has not yet been conclusively resolved, and the semantic status of some double modals remains unclear. Pragmatically, most double modal types have been proposed to be restricted to specific contexts: they are used for 'the negotiation of a speaker's wants or needs' in polite, cautious conversation in order to mitigate face-threatening situations (Mishoe & Montgomery 1994: 12; see also Montgomery 1998;Schneider 2005;Hasty 2015).…”
Section: Introductionmentioning
confidence: 99%